Analisis Produk Lembaga Keuangan Syariah (Kajian Karakteristik Produk Mudlarabah dan Murabahah Pada Lembaga Keuangan Syari’ah) - Siswadi Siswadi; Moh. Nashiruddin Amin (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2021)
Islam prohibits the practice of usury and the accumulation of wealth only by certain parties unfairly. In practical terms, the form of service products and services, the basic principles of the relationship between financial institutions and customers, as well as lawful ways of doing business in Islamic financial institutions, still need to be widely disseminated to the general public. Islamic financial institutions bridge between parties who need funds and parties who have excess funds through financial products and services in accordance with sharia principles that have different characteristics from conventional financial institutions. Syari'ah financial institutions have different characteristics from conventional banks. These characteristics are universal and qualitative. Syari'ah banks operate which must meet these characteristics. Products in Islamic financial institutions can be divided into three major parts, namely: products for raising funds, channeling funds and providing services. The existing products are adapted to the needs of the existing community.